The Influence of Digital Transformation, Logistics Transformation and Digital Literacy on Business Process Innovation and its Implications on Company Performance PT POS INDONESIA - Sirait, Realyta; Waskito, Saptono Kusdanu; Lestiani, Melia Eka (Dinasti Publisher, 2025)
Transformation is a fundamental and comprehensive change in an entity, be it an individual, organization, system, or even an object, which results in different conditions. Transformation has been described by various names, digital transformation, logistics transformation and some also call it leadership transformation. COVID-19, which hit the world, has brought many changes to various business landscapes. In several business sectors this has become the starting point for transformation and PT POS Indonesia is also not free from this. The purpose of this study is to determine and analyze the implementation of digital transformation and logistics transformation that have been implemented by PT POS Indonesia. This research was conducted at the Head Office of PT POS Indonesia located at Jln Cilaki No. 73. This study uses a descriptive quantitative method involving 140 employees with a total population of 215, samples were obtained using the Slovin method with an error rate of 5%, employees work in the logistics courier business directorate and the business development and portfolio management directorate. Data collection was carried out by distributing questionnaires via google form to respondents. The results showed that the average value of each indicator was below 3,400, meeting the requirements for research. Digital transformation with an average value of 3.01, Logistics transformation with an average value of 3.04, Digital Literacy with an average value of 3.05, Business Process Innovation with an average value of 2.95, Company Performance with an average value of 3.27. Research proves that Digital Transformation, Logistics Transformation, and Digital Literacy have a positive and significant effect on Business Process Innovation. Business Process Innovation also has a positive and significant effect on Company Performance. In addition, Digital Transformation, Logistics Transformation and Digital Literacy have been proven to have a positive and significant direct effect on Company Performance. By utilizing technology, work processes in the Logistics sector will be increasingly assisted